From present to the past: The different way of thinking about conservation (A case from design idea for Siola Building, Surabaya) - Defry Agatha Ardianta; Bambang Soemardiono; Tiara Kartika Rini (Institut Teknologi Sepuluh Nopember, 2017)
AbstractThe relation between architecture and the era is always arguable. There are two conditions which describe this relation, at first architecture as a reflection of an era and architecture reflects the timelessness. The later condition commonly becomes a standard of value to judge the architecture is irrelevant with an era by forgetting the first condition. Siola is experiencing both of conditions. A lot of proposals to ‘regain’ its golden time by put intention into heroism or historical background are offered. Many of those efforts focus on how to get the building back like its origin and it’s to be used. Analysis concentrates on‘re-functioning’ which means not to take the function back as its origin but to give the new role by considering the contemporary context? Nostalgic and Romantic aspect has critically seen as the opportunity to take appropriate manner toward better improvement of urban living quality. Siola itself is a landmark which escalating the socio-cultural and economic in Tunjungan corridor. According to historical timeline, many functions are implemented in Siola building before. This historical fact leads the vision that function is changeable within less-changing physical appearance. Furthermore, the main task is to encourage the spirit of people by design strategy and to put it within the building. To trigger the spirit of people evoke the spirit of place.